KALANG, TINJAUAN HISTORIS-ANTROPOLOGIS - Bambang Sulistyanto (BRIN, 1994)
The terms of â€œkalangâ€ substantially mentioned in Old Javanese inscriptions. Itâ€™s meaning oftenly associated with professions in the timber producing or carpentry. Itâ€™s definition drawn from the existence of